2020
DOI: 10.1101/2020.11.03.20221432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spirometric classifications of COPD severity as predictive markers for clinical outcomes: the HUNT Study

Abstract: Rationale GOLD grades based on percent-predicted FEV1 poorly predicts mortality. Studies have recommended alternative expressions of FEV1 for the classification of COPD severity and they warrant investigation. Objective To compare the predictive abilities of ppFEV1 (ppFEV1 quartiles, GOLD grades, ATS/ERS grades), FEV1 z-score (FEV1 z-score quartiles, FEV1 z-score grades), FEV1.Ht-2 (FEV1.Ht-2 quartiles, FEV1.Ht-2 grades), FEV1.Ht-3 (FEV1.Ht-3 quartiles), and FEV1Q (FEV1Q quartiles) to predict clinical outcome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…During the follow-up period, 146, 30, and 56 subjects died because of all causes, respiratory diseases, and cardiovascular diseases, respectively, and 172 and 96 were hospitalized because of COPD and pneumonia, respectively. At baseline, the average age of participants was 63.8 years, 6 of 10 participants were men, and more than half (53.3%) of participants were current smokers ( 15 ). A trend for increasing cumulative incidence of all-cause mortality with worsening categories of classifications of COPD severity was observed ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the follow-up period, 146, 30, and 56 subjects died because of all causes, respiratory diseases, and cardiovascular diseases, respectively, and 172 and 96 were hospitalized because of COPD and pneumonia, respectively. At baseline, the average age of participants was 63.8 years, 6 of 10 participants were men, and more than half (53.3%) of participants were current smokers ( 15 ). A trend for increasing cumulative incidence of all-cause mortality with worsening categories of classifications of COPD severity was observed ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We defined expressions of FEV 1 such as ppFEV 1 , FEV 1 z -score, FEV 1 ⋅ Ht −2 , FEV 1 ⋅ Ht −3 , and FEV 1 Q (described in detail in Reference 15 ) as suggested by the previous studies ( 1 – 3 , 5 , 6 , 8 , 9 , 16 ). The Global Lung Function Initiative 2012 reference equation was used to calculate ppFEV 1 , ppFVC, FEV 1 z -scores, and FVC z -scores ( 11 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously used both approaches in the same population ( 24 ), and they both performed similarly; therefore, only Z -transformed values were added to the model. Previous studies reported that FEV1 standardised with height might be a more reliable measure for predicting survival in the elderly population ( 56 , 59 61 ). We have previously also showed a strong dose–response relationship between lung function (defined as FEV1/height 3 ) and cardiovascular mortality in our recent study ( 39 ).…”
Section: Discussionmentioning
confidence: 99%